2017
DOI: 10.5144/0256-4947.2017.148
|View full text |Cite
|
Sign up to set email alerts
|

A novel WDR62 mutation causes primary microcephaly in a large consanguineous Saudi family

Abstract: BACKGROUNDPrimary microcephaly (MCPH) is a rare developmental defect characterized by impaired cognitive functions, retarded neurodevelopment and reduced brain size. It is genetically heterogeneous and more than 17 genes so far have been identified that are associated with this disease.OBJECTIVETo study the genetic defect in a consanguineous Saudi family with primary microcephaly.DESIGNCross-sectional clinical genetics study of a Saudi family.SETTINGMedical genomics research center.PATIENTS AND METHODSBlood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 45 publications
0
18
0
3
Order By: Relevance
“…Over 40 pathogenic mutations in WDR62 have already been published. In addition to microcephaly, a wide range of cortical malformations was also described in these patients (Bacino et al 2012;Banerjee et al 2016;Bastaki et al 2016;Bhat et al 2011;Farag et al 2013;Sajid Hussain et al 2013;Kousar et al 2011;McDonell et al 2014;Memon et al 2013;Miyamoto et al 2017;Murdock et al 2011;Najmabadi et al 2011;Nardello et al 2018;Naseer et al 2017;Poulton et al 2014;Rupp et al 2014;Wang et al 2017).…”
Section: Introductionmentioning
confidence: 89%
“…Over 40 pathogenic mutations in WDR62 have already been published. In addition to microcephaly, a wide range of cortical malformations was also described in these patients (Bacino et al 2012;Banerjee et al 2016;Bastaki et al 2016;Bhat et al 2011;Farag et al 2013;Sajid Hussain et al 2013;Kousar et al 2011;McDonell et al 2014;Memon et al 2013;Miyamoto et al 2017;Murdock et al 2011;Najmabadi et al 2011;Nardello et al 2018;Naseer et al 2017;Poulton et al 2014;Rupp et al 2014;Wang et al 2017).…”
Section: Introductionmentioning
confidence: 89%
“…Mutations in the WDR62 can cause severe cerebral cortical abnormalities, including microcephaly, cerebral gyrus hypertrophy with cortical thickening and dysplasia of corpus callosum [6,8,9], all inherited in an autosomal recessive. A number of neurobehavioral abnormalities have been reported, including psychomotor developmental delay, seizure, aggression and irritability [9][10][11]. In addition, some case reports claimed that WDR62 mutation can also cause skin changes [12].…”
Section: Case Presentationmentioning
confidence: 99%
“…The majority of mutations found in WDR62 revealed that these are responsible for approximately 10% of cases of microcephaly. Homozygous or heterozygous mutations in WDR62 both cause MCPH with or without cortical malformations (Naseer et al, 2017). Patients with these mutations have a head circumference ranging from normal to severe.…”
Section: (Ii) Mcph2 (Wdr62)mentioning
confidence: 99%